Chronic fatigue syndrome: a follow up study. Issue 5 (May 1994) - Bonner, D; Ron, M; Chalder, T; Butler, S; Wessely, S
Abstract : Forty-six of 47 patients diagnosed as having chronic fatigue and offered treatment four years previously were followed up. Twenty-nine patients were interviewed, three patients refused an interview, and information on the remaining 14 was obtained from their general practitioners. All the instruments used at interview had been used in the initial study. The long-term prognosis for patients with chronic fatigue syndrome who have initially responded to treatment is good. Spontaneous recovery in those who declined or who did not benefit from treatment is unlikely. Patients who continue to fulfil the criteria for chronic fatigue syndrome four years after they were initially diagnosed are likely to have had more somatic disorders, to have been more fatigued, and to have had a previous psychiatric history when they were initially assessed.